MAM kinases: physiological roles, related diseases, and therapeutic perspectives—a systematic review - A. Anjana Mohan; Priti Talwar (Cellular & Molecular Biology Letters)
Abstract Mitochondria-associated membranes (MAMs) are tethering regions amid the membranes of the endoplasmic reticulum (ER) and mitochondria. They are a lipid raft-like structure occupied by various proteins that facilitates signal transduction between the two organelles. The MAM proteome participates in cellular functions such as calcium (Ca2+) homeostasis, lipid synthesis, ER stress, inflammation, autophagy, mitophagy, and apoptosis. The human kinome is a superfamily of homologous proteins consisting of 538 kinases. MAM-associated kinases participate in the aforementioned cellular functions and act as cell fate executors. Studies have proved the dysregulated kinase interactions in MAM as an etiology for various diseases including cancer, diabetes mellitus, neurodegenerative diseases, cardiovascular diseases (CVDs), and obesity. Several small kinase inhibitory molecules have been well explored as promising drug candidates in clinical trials with an accelerating impact in the field of precision medicine. This review narrates the physiological actions, pathophysiology, and therapeutic potential of MAM-associated kinases with recent updates in the field. Graphical Abstract